Student gadget addiction behavior in the perspective of respectful framework - Wardhani, Frida Putri (Universitas Negeri Padang, 2018)
Someone who use gadget in the right way will get benefits. Meanwhile, people who can not control gadget itself will get some negative impact.Â One of negative impact is people will become addicted in gadget. This research finds the behavior of gadget addicted for students based on respectful framework. This research is qualitative descriptive design. Research instruments are interview, observation, and documentation. The primary informants come from two students of SMP Negeri 1 Karangrejo who also being the subject of research. Meanwhile, the proponent informant come from parents from two students who are the subject of research and school counselor from SMP Negeri 1 Karangrejo. It's meant assessment by respectful framework has differences behavior and factors that influence student behaviors.